2012
DOI: 10.4194/1303-2712-v12_3_09
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A study was conducted to determine the comparative reproductive, growth performances and nutrient utilization of Clarias gariepinus and its hybrid "heteroclarias" using ovaprim and pituitary extract of male and female C. gariepinus. The experimental broodstocks consisted of 6 female C. gariepinus (2 each were induced separately with ovaprim, male pituitary of C. gariepinus and female pituitary of C. gariepinus), 3 male C. gariepinus and 3 male Heterobranchus bidorsalis. 2 female C. gariepinus induced with synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
3
5
0
Order By: Relevance
“…When reproductive performances of the two species were evaluated, the eggs of C. gariepinus had higher rate of fertilization and hatching over the eggs of C. batrachus in both its control and hybrid groups that might be related to the high fecundity of the C. gariepinus species (Table 1) agrees with authors (Ndimele and Owodeinde, 2012;Hassen et al, 2011;Richter, 1995;Mollah and Tan, 1983) Though fertilization and hatching in pure batrachus (Cb x Cb) strain was lower as compared to pure gariepinus (Cg x Cg) strain, the results obtained in this study is also comparable with earlier authors who achieved higher performance in the same species (Chaturvedi and Pandy, 2012;Srivastava et al, 2012;Goswami, 2007;Mahabatra, 2004). Crossbreeding is used to achieve improved traits (heterosis), minimize inbreeding and obtain better hybrids (Mires, 1982;Bartley et al, 1997;Dong and Yuan, 2002;Anita, 2004;Jothilakshmanan and Karal Marx, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When reproductive performances of the two species were evaluated, the eggs of C. gariepinus had higher rate of fertilization and hatching over the eggs of C. batrachus in both its control and hybrid groups that might be related to the high fecundity of the C. gariepinus species (Table 1) agrees with authors (Ndimele and Owodeinde, 2012;Hassen et al, 2011;Richter, 1995;Mollah and Tan, 1983) Though fertilization and hatching in pure batrachus (Cb x Cb) strain was lower as compared to pure gariepinus (Cg x Cg) strain, the results obtained in this study is also comparable with earlier authors who achieved higher performance in the same species (Chaturvedi and Pandy, 2012;Srivastava et al, 2012;Goswami, 2007;Mahabatra, 2004). Crossbreeding is used to achieve improved traits (heterosis), minimize inbreeding and obtain better hybrids (Mires, 1982;Bartley et al, 1997;Dong and Yuan, 2002;Anita, 2004;Jothilakshmanan and Karal Marx, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Apart from the genetic factors, the non-genetic factors like the culture system and condition like water temperature, salinity, pH and alkalinity also plays a major role in the success of hybridization (Rahman et al 2012). Similar suggestion was given by Ndimele and Owodeinde (2012), who described that the pure breeds tolerate more stress than the hybrids.…”
Section: Discussionsupporting
confidence: 75%
“…This agreed with (Hossain et al 2012) who worked on C. gariepinus fish induced with synthetic and natural hormone. The broodstock induced with pituitary gland had higher survival (82.31%) after six weeks compared to the broodstock induced with ovaprim (79.68%), this agreed with (Chattopadhyay, 2018) The growth of the larvae monitored for six weeks revealed a significant difference (P<0.05) among the treatments at the early stage, meanwhile, there was no significant difference in the SGR and RGR, this agreed with (Abdul et al, 2017) who recorded a similar growth rate after the feeding trial for 28 days, the same trend was reported by Ndimele and Owodeinde (2012). However, Ikechukwu et al (2019) explained that the growth among the fishes treated with ovaprim and pituitary gland extract was not significantly different.…”
Section: Discussionsupporting
confidence: 85%
“…There is a paucity of reports on C. macromystax potentials of culture in captivity and an estimate of broodstock yield through gonadosomatic indices, partly due to the high cost of the fish [10][11][12]. The current study was designed to evaluate the reproductive traits of C. gairepinus and C. macromystax and their relationship with broodstock sizes [13,14].…”
Section: Introductionmentioning
confidence: 99%